The Effect Of Using Stem-PJBL Toward Science Literacy Ability And Collaboration Skill Of Prospective Science Teachers: Study On Subject Of Matter And Energy - Yunus, Sitti Rahma; Arif, Rifda Nur Hikmahwati; Yanto, Nurfitra; Sarina, Sarina; Pertiwi, Andini; Alim, Muhammad Harisah (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Negeri Makassar, 2024)
This research aims to analyze the level of science literacy ability and collaboration skill of prospective science teachers in the course of Matter and Energy and analyze the influence of STEM-PJBL learning on literacy abilities science and collaboration skills. This research is a pre-experiment with the research design used was One-Shot Case Study. In this design, students are given treatment, then observations are made about collaboration skill and they are given a scientific literacy ability test. The population in this study were all students of the faculty of Mathematics and Natural Science, Universitas Negeri Makassar at the Science Education Study Program in the even semester of the 2022/2023 academic year, while the sample in this study was students in the regular class of the 3rd semester of the 2022/2023 academic year which consisted of 2 classes that programmed the course of Matter and Energy. The regular class 01 as an experimental class and regular class 02 as a replication class. The research instruments used to measure collaboration skills are non-test instruments in the form of collaboration skills observation sheets and scientific literacy test instruments in the form of multiple choices. The results of descriptive statistical analysis show that the level of scientific literacy skills is in high category and the level of collaboration skills of prospective science teachers is in the very high category. The results of the inferential analysis show that the application of STEM-PJBL influences the scientific literacy abilities and collaboration skills of prospective science teachers in substance and energy courses. These results show that STEM-PJBL learning can be applied to other subjects because it can improve scientific literacy skills and collaboration skills of prospective teachers. It can be implemented to examine the effectiveness of this model in similar variables on the other subjects.